Associations of mental health with cardiovascular risk phenotypes and adiposity in adolescence: A cross‐sectional community‐based study. (20th May 2018) - Lycett, Kate; McNamara, Clare; Mensah, Fiona K; Burgner, David; Kerr, Jessica A; Muller, Josh; Wake, Melissa
Abstract : Aim: Cardiovascular disease and mental illness commonly co‐occur in later life, but it is unknown how early these associations arise. We aimed to determine the extent to which: (i) childhood mental health is associated with functional and structural cardiovascular risk phenotypes and adiposity in late childhood/adolescence, and (ii) associations between mental health and cardiovascular phenotypes may be explained by differential body mass index. Methods: This cross‐sectional study drew on three longitudinal community‐based cohort studies (two enriched for overweight/obesity) in metropolitan Melbourne, Australia, with harmonized follow‐up in 2014. Mental health exposures included emotional and behavioural problems (Strength and Difficulties Questionnaire) and psychosocial health and general well‐being (Pediatric Quality of Life Inventory (PedsQL)), which were assessed by self‐ and parent‐proxy report. Cardiovascular risk phenotypes and adiposity measures included mean arterial pressure, pulse wave velocity, carotid artery intima‐media thickness, retinal arterioleto‐venule ratio, waist circumference, % body fat, and BMI z‐score. We used multivariable linear regression models, adjusting for age, sex and neighbourhood disadvantage, to examine associations. Results: Of the 364 participants (mean age 14.7, standard deviation 2.0, years), 30% were overweight and 16% obese. All adiposity indicators were positively associated with higher behavioural/emotional problems and poorer psychosocial health and negatively associated with better ratings of positive general well‐being, as reported by parents and children (all P ≤ 0.03). However, there was little evidence that cardiovascular functional or structural phenotypes varied by mental health. Conclusions: By late childhood/adolescence, mental health is strongly associated with adiposity but not with cardiovascular structure or function. This suggests that the known relationship between these constructs may not develop until early or mid‐adulthood.